2015
DOI: 10.1210/en.2015-1799
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Promotes Functional Angiogenesis in a Mouse Model of Critical Limb Ischemia Through Activation of Proangiogenic MicroRNAs

Abstract: Current therapeutic strategies for the treatment of critical limb ischemia (CLI) have only limited success. Recent in vitro evidence in the literature, using cell lines, proposes that the peptide hormone ghrelin may have angiogenic properties. In this study, we aim to investigate if ghrelin could promote postischemic angiogenesis in a mouse model of CLI and, further, identify the mechanistic pathway(s) that underpin ghrelin's proangiogenic properties. CLI was induced in male CD1 mice by femoral artery ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 62 publications
1
32
0
1
Order By: Relevance
“…Ever since its discovery in 1999 (17), ghrelin has emerged as an important therapeutic modulator of cardiac function in health and disease (18). Whereas the exact mechanisms that underpin the cardioprotective properties of ghrelin remain to be fully elucidated, various groups have shown that ghrelin prevents MI-induced sympathetic activation (6,7,19,20), inhibits myocardial apoptosis (21), promotes angiogenesis (22,23), reduces cardiac cachexia and dysfunction (24), preserves cardiac contractility (25), and attenuates cardiac remodeling (26). Although ghrelin is known to modulate coronary vasculature tone directly, at least in animal models, the few reports, to date, do not agree as to whether ghrelin dilates or constricts coronary vessels (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Ever since its discovery in 1999 (17), ghrelin has emerged as an important therapeutic modulator of cardiac function in health and disease (18). Whereas the exact mechanisms that underpin the cardioprotective properties of ghrelin remain to be fully elucidated, various groups have shown that ghrelin prevents MI-induced sympathetic activation (6,7,19,20), inhibits myocardial apoptosis (21), promotes angiogenesis (22,23), reduces cardiac cachexia and dysfunction (24), preserves cardiac contractility (25), and attenuates cardiac remodeling (26). Although ghrelin is known to modulate coronary vasculature tone directly, at least in animal models, the few reports, to date, do not agree as to whether ghrelin dilates or constricts coronary vessels (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Both miR-126-3p and -5p are also highly expressed in ECs where they promote angiogenesis by stimulating EC proliferation and VEGF signaling and regulating leukocyte adhesion [46][47][48][49]. Inhibition of miR-126-3p was shown to decrease recovery after myocardial infarction and hindlimb ischemia in mice [47,50,51]. Furthermore, miR-126 levels are decreased in patients with ischemic coronary artery disease [52].…”
Section: Micrornasmentioning
confidence: 99%
“…Взаимосвязь между изменениями L/Gh и массой органов и тканей может быть обусловлена участием лептина и грелина в регуляции ангиогенеза и формировании фиброзных изменений, которые наблюдаются при ожирении и метаболическом синдроме. Причем была показана как проангиогенная, так и антифибротическая роль грелина in vivo и in vitro за счет активации Bcl-2 (белок семейства регуляторов апоптоза) сигнального пути и редукции апоптоза [17]. На этом фоне системное введение грелина мышам, получающим обогащенный жирами рацион, способствовало увеличению сывороточного VEGF (фактор роста эндотелия) и снижению сывороточных концентраций лептина и NO (окись азота II) [19].…”
Section: биомаркеры гиперлипидемииunclassified